Chryseobacterium frigidisoli sp. nov., a psychrotolerant species of the family Flavobacteriaceae isolated from sandy permafrost from a glacier forefield - Bajerski, Felizitas; Ganzert, Lars; Mangelsdorf, Kai; Padur, Lisa; Lipski, André; Wagner, Dirk (International Journal of Systematic and Evolutionary Microbiology, 2013)
During diversity studies of the glacier forefields of the Larsemann Hills, East Antarctica, a novel psychrotolerant, non-motile Gram-negative, shiny yellow, rod-shaped, aerobic bacterium, designated strain PB4T was isolated from a soil sample. Strain PB4T produces indole from tryptophan and hydrolyses casein. It grows between 0 and 25 °C with an optimum growth temperature of 20 °C. A wide range of substrates are used as sole carbon sources and acid is produced from numerous carbohydrates. The major menaquinone is MK-6. Identified polar lipids are ethanolamines and ornithine lipids. Major fatty acids (>10 %) are iso-C15 : 0 (13.0 %) and iso-2OH-C15 : 0 (51.2 %). G+C content is 33.7 mol%. The polyamine pattern is composed of sym-homospermidine (25.1 µmol g−1 dry weight), minor amounts of cadaverine (0.2 µmol g−1 dry weight) and spermidine (0.4 µmol g−1 dry weight) and traces of putrescine and spermine (<0.1 µmol g−1 dry weight). Strain PB4T had highest 16S rRNA gene similarities with the type strains of Chryseobacterium humi (97.0 %) and Chryseobacterium marinum (96.5 %). Considering phenotypic and genotypic characterization, strain PB4T represents a novel species in the genus Chryseobacterium (family Flavobacteriaceae), for which the name Chryseobacterium frigidisoli sp. nov. is proposed. The type strain is PB4T ( = DSM 26000T = LMG 27025T).